Respostas

A melhor resposta!
2013-07-17T23:47:01-03:00
(i) 2c + 5t + 8m = 390
(ii) c + 2t + 3m = 160
(iii) c + 4t + 7m = K

multiplicando (ii) por 2

2c = 320 - 4t - 6m

substituindo em (i)

320 - 4t - 6m + 5t + 8m = 390
t + 2m = 70........(iv)

somando (ii) + (iii) - (i)

c + 4t + 7m + c + 2t + 3m - 2c - 5t - 8m = K + 160 - 390
t + 2m = K - 230.......(v)

substituindo (iv) em (v)

70 = K - 230

K = 300

3 3 3
2013-07-18T09:51:19-03:00
(i) 2c + 5t + 8m = 390
(ii) c + 2t + 3m = 160
(iii) c + 4t + 7m = K

 (ii) x 2

2c = 320 - 4t - 6m


320 - 4t - 6m + 5t + 8m = 390
t + 2m = 70_____(iv)

 (ii) + (iii) - (i)

c + 4t + 7m + c + 2t + 3m - 2c - 5t - 8m = K + 160 - 390
t + 2m = K - 230_____(v)


70 = K - 230

K = 300
 
1 1 1